A Field Study Update on Organizational Satanism and Setianism in the United States - Foertsch, Steven (Review of religious research, 2022)
Background: With recent attention to the organizational dynamics of contemporary Satanism, updated information on Satanic and Setian organizations is imperative for the field. Purpose: The purpose of this research note is to update the literature surrounding Satanism and Setianism with new organizational and administrative information, which will help scholars studying these groups in developing new theoretical frameworks and interpretations. Methods: A snowball sample interview, participant observation, and ethnographic study was conducted. In person field work was done primarily in Austin, TX, and New York, NY, where occult bookstores, wicca stores, online group pages/forums, Satanic gatherings, and goth clothing shops were frequented for a portrayal of "lived Satanism."ResultsFindings elaborate on the authority structures of five Satanic and Setian organizations, and a long considered defunct Satanic group called the Church of Satanic Brotherhood is uncovered. Participants also elaborate on the previous schisms within the Satanic niche. Conclusions and Implications: Field note recommendations are given to future researchers working in Satanic studies. The organizational findings inform future research and theoretical innovations, including religious organization ecology (ROE) theory﻿.